Pemberian Kombinasi Tablet Fe dan Jus Jambu Biji Merah terhadap Peningkatan Kadar Haemoglobin Ibu Hamil dengan Anemia Ringan - Yuliva, Yuliva; Zaimy, Silvi; Rahayu, Eka Sri; Eravianti, Eravianti (Poltekkes Kemenkes Padang, 2023)
One of the pharmacological therapies for anemia is giving Fe supplements every day, and non-pharmacological therapy by consuming foods high in iron and vitamin C such as red guava. The aim of this study was to determine the effect of giving a combination of fe tablets and red guava juice on increasing hemoglobin in pregnant women with mild anemia. This type of research is analytical with a Quasi Experimental Research design. The population in this study were pregnant women totaling 14 pregnant women. The research was conducted on the intervention group by giving Fe tablets and red guava juice, while the control group was only given Fe tablets. Giving 330 ml of red guava juice every day for 14 days with a composition of 100 ml of water, and 250 grams of red guava without sugar and sweetened condensed is given in the afternoon at 4.00 pm. The results of the research were that the average hemoglobin level before giving fe tablets was 10.08 gr/dL and after giving it was 10.55 gr/dL, before giving red guava juice and fe tablets it was 10.30 gr/dL and after giving red guava juice and fe tablets it was 11.18 gr/dL, p value = 0.036 (p < 0.05) with an average difference (Mean Difference) of 0.63 (11.18 – 10.55).There is a significant difference in hemoglobin levels after administering fe tablets accompanied by red guava juice towards increasing hemoglobin levels in pregnant women. It is expected that pregnant women will consume red guava juice and fe tablets regularly so that they can increase Hb levels in pregnant women with anemia.